PECULIARITIES OF 6Li AND 7Li ISOTOPES INTERACTION WITH LIGHT NUCLEI - Zhusupov, М.А.; Kabatayeva, R.S. (Recent Contributions to Physics, 2011)
Mechanisms of particles interaction with lithium isotopes and lithium transfer reactions with  nucleus formation are investigated. Spectroscopic factors in 6Li+t  and 7Li+d channels are calculated.